Efektivitas Dosis NPK Mutiara dan Pupuk Kandang Kambing terhadap Pertumbuhan dan Hasil Tanaman Tomat (Solanum lycopersicum L.) - Juhri Rosadi, Mohammad; Furoidah, Nanik (JURNAL AGROPLANT, 2025)
The need for tomatoes increases every year, but plant productivity is less stable due to several factors such as season, soil fertility and nutrition. This study aims to determine the effectiveness of the dose of NPK pearl and goat manure on the growth and yield of tomato plants (Solanum lycopersicum L.). This study was conducted in Karangtemplek Village, Ambulu District, Jember, East Java at an altitude of 70 meters above sea level, starting from December 2023 to March 2024. This study used a factorial Randomized Block Design with 3 replications. The first factor is the dose of NPK pearl fertilizer with 4 levels, namely: N0 = 0 g / plant, N1 = 5 g / plant, N2 = 7 g / plant, N3 = 9 g / plant. The second factor is the dose of goat manure with 4 levels, namely: K0 = 0 g / plant, K1 = 100 g / plant, K2 = 125 g / plant, K3 150 = g / plant. The data obtained were analyzed by analysis of variance, if there was a significant difference in the treatment, then continued with the Duncan test at the 5% level. The results showed that the NPK pearl dose of 9 g/plant had the best effect on plant height and stem diameter, the NPK dose of 5 g - 7 g/plant was effective in the number of leaves, flowering age, number of fruits, fruit weight per unit and fruit weight per plant. The goat manure dose of 125 g - 150 g/plant was more effective in its effect on plant height and fruit volume. The interaction between NPK pearl fertilizer and goat manure had no significant effect on all observation parameters.